Sparing of muscle mass and function by passive loading in an experimental intensive care unit model. (30th January 2013) - Renaud, Guillaume; Llano‐Diez, Monica; Ravara, Barbara; Gorza, Luisa; Feng, Han‐Zhong; Jin, Jian‐Ping; Cacciani, Nicola; Gustafson, Ann‐Marie; Ochala, Julien; Corpeno, Rebeca; Li, Meishan; Hedström, Yvette; et al.
Key points: Early physical mobilization of mechanically ventilated intensive care unit (ICU) patients can reduce the length of stay in the ICU and hospital and improve muscle strength and functional outcomes. A unique experimental rat ICU model has been used to study the effects and underlying mechanisms of unilateral passive mechanical loading on skeletal muscle size and function at durations varying between 6 h and 2 weeks. Passive mechanical loading attenuated the loss of muscle mass and force‐generation capacity associated with the ICU intervention. The maintained muscle mass and function by passive loading is probably due to lower oxidative stress and a reduced loss of the molecular motor protein myosin. The beneficial effects of passive mechanical loading on muscle size and function strongly support the importance of early and intense physical therapy in immobilized ICU patients. Abstract The response to mechanical stimuli, i.e. tensegrity, plays an important role in regulating cell physiological and pathophysiological function, and the mechanical silencing observed in intensive care unit (ICU) patients leads to a severe and specific muscle wasting condition. This study aims to unravel the underlying mechanisms and the effects of passive mechanical loading on skeletal muscle mass and function at the gene, protein and cellular levels. A unique experimental rat ICU model has been used allowing long‐term (weeks) time‐resolved analyses of the effects of standardized unilateral passive mechanical loading on skeletal muscle size and function and underlying mechanisms. Results show that passive mechanical loading alleviated the muscle wasting and the loss of force‐generation associated with the ICU intervention, resulting in a doubling of the functional capacity of the loaded versus the unloaded muscles after a 2‐week ICU intervention. We demonstrate that the improved maintenance of muscle mass and function is probably a consequence of a reduced oxidative stress revealed by lower levels of carbonylated proteins, and a reduced loss of the molecular motor protein myosin. A complex temporal gene expression pattern, delineated by microarray analysis, was observed with loading‐induced changes in transcript levels of sarcomeric proteins, muscle developmental processes, stress response, extracellular matrix/cell adhesion proteins and metabolism. Thus, the results from this study show that passive mechanical loading alleviates the severe negative consequences on muscle size and function associated with the mechanical silencing in ICU patients, strongly supporting early and intense physical therapy in immobilized ICU patients.